Efficacy of additional radiofrequency ablation after transcatheter arterial chemoembolization for intermediate hepatocellular carcinoma. Issue 4 (15th September 2015) - Azuma, Seishin; Asahina, Yasuhiro; Nishimura‐Sakurai, Yuki; Kakinuma, Sei; Kaneko, Shun; Nagata, Hiroko; Goto, Fumio; Ootani, Satoshi; Kawai‐Kitahata, Fukiko; Taniguchi, Miki; Murakawa, Miyako; Watanabe, Takako; et al.
Abstract : Aim: For intermediate hepatocellular carcinoma (HCC), transcatheter arterial chemoembolization (TACE) therapy is recommended in the guidelines as a monotherapy, although TACE is a non‐curative therapy. The aims of the present study were to evaluate the efficacy of adding radiofrequency ablation (RFA) to TACE in patients with intermediate HCC, and to identify the factors that were associated with favorable survival in these patients. Methods: Fifty‐nine patients with intermediate HCC were enrolled in this retrospective study. Thirty‐nine patients were treated with TACE alone and 20 patients were treated with additional RFA after TACE. Results: The recurrence‐free survival rates at 0.5, 1 and 2 years for the additional RFA group were 32%, 19% and 13%, respectively, and these were significantly higher than those of the TACE group (8%, 3% and 0%, respectively; log–rank test, P = 0.001). The cumulative survival rates of the additional RFA group were significantly higher than those of the TACE group (log–rank test, P = 0.002), although this significant difference was not found in the subgroup of treatment naive patients because of small sample size. Multivariate analysis indicated male sex, lower total bilirubin, lower α‐fetoprotein, lower des‐γ‐carboxyprothrombin, newly recurrent HCC nodules within the last 12 months and additional RFA as independent factors that were significantly associated with favorable overall survival. Conclusion: Additional RFA of nodules insufficiently treated by TACE is effective therapy for obtaining favorable disease‐free survival in patients with intermediate HCC, and leads to better overall survival particularly in recurrent patients.